The Design of Mooring Dolphin Layout and Mooring Line Tension Analysis - Haryo Dwito Armono; Yoffan Ramadhan; Sholihin Sholihin (International Journal of Offshore and Coastal Engineering, 2017)
Some marine industries choose to set up their activities in the coastal area northern part of Java Island, Indonesia, by considering the calmness of the Java Sea environment. A special terminal for liquid bulk cargo to transport fuel oil is being planned for construction in Sedayu Lawas village, Lamongan district, East Java Province. The ship carrying cargo oil require a pier and jetty in sufficient depth for loading and unloading. The jetty need to be enhanced to support more equipment for ship to port, which include breasting dolphin, mooring dolphin, trestle, and causeway. In this respect a study is carried out to review the stress analysis of the mooring lines (ropes) attached to jetty for various mooring dolphin layout and arrangements. The metocean data such as wind and tides in the areas were processed and analyzed. The layout of the ship and mooring dolphin rope angle were designed in accordance with OCIMF code. The stress analysis of mooring rope for various layout mooring dolphin has been analyzed to determine whether the design layout is safe during operation. The rope stress were analyzed using time domain dynamic analysis for 10,800 seconds. The safety of ship during loading for various rope condition were presented. It is suggested that all ropes should be attached to mooring dolphin for ship and port safety.